Effect of homocysteine and antioxidants on peroxidation lipid of essential hypertension in Central Java Indonesia - Rizka H Asdie, Mohammad Hakimi, Sunarti Ria Maudisa (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2008)
Background: The increase in the homocysteine level is related to the heightening of blood pressure and hypertension risk. Hyperhomocysteinemia encourages the production of free radical which can oxidi2e lipid. Lipid peroxidation can be prevented by several antioxidant such as vitamin C and E.Objective: This study is aimed at finding out the nature of the interaction effect between homocysteine and antioxidant vitamins on malondialdehyde level in essential hypertension.Method: This study was a case-control nested to NSurveiliance of Non-Communicable DiseasesN in Purworejo, Central Java. The subjects were men, essential hypertension and 20-60 years old that have normal value of urine creatinine, blood glucose, cholesterol and triacylglycerol. They have been take antihypertension drugs. The blood glucose, cholesterol, triacylglycerol, urine creatinine, vitamin C and malondialdehyde (MDA) levels were measured by spectrophotometer. Whereas the total plasma homocysteine and vitamin E were determined by HPLC.Result: The homocysteine level in the cases was higher than that of the control and was significantly different (P = 0,027). There were not significantly different of the vitamin C, vitamin E, and MDA between the cases and the control (P=0.538, P=0.390, and P=0.536) respectively. The MDA was positively correlated with homocysteine (P=O.OOOI and negatively correlated with vitamin E (P=0.029), but it was not negatively significant correlated with vitamin C (P=0.0671. The correlation had r= 0.417; R2=0.174 and F=7.713.Conclusion: The high homocysteine level is one of hypertension risk factors and its effect through oxidative stress. The effect can be prevented by antioxidant vitamins, specially vitamin E.Key words: homocysteine - antioxidants - peroxidation lipid - essential hypertension - avanese